If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(5 + 5m) = 75 (5 * -3 + 5m * -3) = 75 (-15 + -15m) = 75 Solving -15 + -15m = 75 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -15m = 75 + 15 Combine like terms: -15 + 15 = 0 0 + -15m = 75 + 15 -15m = 75 + 15 Combine like terms: 75 + 15 = 90 -15m = 90 Divide each side by '-15'. m = -6 Simplifying m = -6
| 1x+8=5 | | -6(10+2x)=-192 | | 3s^2+7s^2-18s-42=0 | | 3x-6=x-3 | | k-9=11 | | 0.6(-6.53-2x)=-0.4x | | 8x-9=3-2x | | (x-9)(3x-1)=-52x-39 | | 2(x-1)-6= | | 7sin^2(x)-3=0 | | 1-(3x+4)2=(4x-1)2-(5x+2)2 | | x-7=7x+5 | | -2.0p=5(10-0.5p) | | 6-4x-7x^3=0 | | (t+2)(t-3)=6 | | 5(3z-1)-3(z+5)=9(z+1) | | 6v-7=-9+7v | | 8w^2-18+9=0 | | 264=xy+(7(y+1))+(2(y+2)) | | abs(x-5)=abs(5x+4)-1 | | abs(x-5)=abd(5x+4)-1 | | x-3+x+x+3=38 | | 3x+.2=2x | | 3s+s=196 | | 9x-22=y | | 2.5x-2(8x-4)x=3.1 | | 5s+s=234 | | 4x^2+y^2-8x-4y+4=0 | | x-3+x+x+3=32 | | 10n-0.375=0.7n-0.375 | | 3(p-4)=2p+7 | | 3cos^2(x)-14cos(x)+8=0 |